Design Of Smart Hydroponics Based On Raspberry Pi 3 - Diah Aryani; Ignatius Agus Supriyono; Hani Dewi Ariessanti; Shine Pintor Siolemba Patiro; Ichyan Holilan (PETIR, 2021)
The development of hydroponic suitable methods is currently quite good, the utilization of the narrow land availability and the people's attractiveness to hydroponics are the reasons for the developing hydroponic suitable method. However, in its development, there is less land with soil growing media, there is a pattern of farming using water media, namely hydroponics (Hydroponics). Hydroponic cultivation must pay attention to the elements that plants need, such as providing special nutrition to plants. The provision of nutrition that is done manually often results in irregular nutrition in hydroponics which results in disruption of hydroponic plant growth and harvest is not optimal. Research on the Smart Hydroponics System based on the Raspberry Pi 3 using the tidal hydroponic system can make it easier for every human being who wants to grow crops especially who are busy with work activities. With the research methodology using flowchart design methods and system block diagrams, where the Raspberry Pi 3 Mini Computer is used to control pumps in the circulation of hydroponic plant nutrients. Set the nutrient pump On / Off, display a Video Stream from the Cyberlink C170 webcam to check the progress of fruit or vegetable crops ready for harvest. Everything is done remotely via the Web Interface at the Manapu location so that with this research, monitoring can be carried out and it is easier to provide the elements needed by plants